Microstructural evolution and its influence on the magnetic properties of CoFe2O4 powders during mechanical milling - Boothroyd, C. B. (2011)
A high coercivity of up to 5.1 kOe was induced in a large-grained CoFe2O4 powder after milling for a short time (1.5 h). It was found that the initial grain (particle) size played an important role in the microstructural evolution and in the magnetic properties of the milled CoFe2O4 materials. The milling-induced microstructural evolution was analyzed using x-ray diffraction and transmission electron microscopy. The results indicated that the milling-induced high coercivity was associated with the highly-strained and defective microstructure. The enhancement in magnetic anisotropy was observed in large-grained CoFe2O4 after milling, which might be mainly attributed to the stress anisotropy. In order to understand the coercivity mechanisms, detailed magnetic studies were carried out by the investigation of the field-dependent magnetization (demagnetization) behaviors and the magnetization reversal processes based on both the micromagnetic model and the phenomenological model. The results revealed that a domain wall pinning-controlled mechanism was responsible for the milling-induced high coercivity in CoFe2O4 materials.